ANALISIS KOMPARASI USAHA TANI PADI ORGANIK DAN PADI KONVENSIONAL DI DESA SIDAN KABUPATEN GIANYAR - Stefanus Jemeon; Ketut Arnawa; Cening Kardi, (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2024)
Organic production systems generally have lower yields than conventional systems, but the profitability of organic farming systems is higher than that of conventional farming systems due to the high selling price of organic products. This study aims to analyze the profitability of organic rice farming in Sidan Village, Gianyar District, Gianyar Regency, to analyze the profitability of conventional rice farming in Sidan Village, Gianyar District, Gianyar Regency and the advantages of organic rice and conventional rice in Sidan Village, Gianyar District, District Gianyar. This research was conducted in Sidan Village, Gianyar District, Gianyar Regency and was conducted for 3 months starting from March - May 2024. The sample used was 60 people. Data analysis used in this research is quantitative analysis. Quantitative analysis is used to analyze revenue, costs, and profits of farming, analysis of farm income, and analysis of efficiency of farming costs. The results showed that the profit of organic rice farming in Sidan Village, Gianyar District was IDR 6,108,191.19/ 24.24 acres. The profit of conventional rice farming in Sidan Village, Gianyar District is IDR 4,881,264.71/ 22.41 are. Comparison (Comparative) of the Profits of Organic Rice and Conventional Rice obtained a significant profit value with Sig. (2-tailed) of 0.000 <0.05, it can be interpreted that there is a significant difference in the profits of organic rice farming and conventional rice farming.